2015
DOI: 10.1186/s12884-015-0587-z
|View full text |Cite
|
Sign up to set email alerts
|

The study of women, infant feeding and type 2 diabetes after GDM pregnancy and growth of their offspring (SWIFT Offspring study): prospective design, methodology and baseline characteristics

Abstract: BackgroundBreastfeeding is associated with reduced risk of becoming overweight or obese later in life. Breastfed babies grow more slowly during infancy than formula-fed babies. Among offspring exposed in utero to maternal glucose intolerance, prospective data on growth during infancy have been unavailable. Thus, scientific evidence is insufficient to conclude that breastfeeding reduces the risk of obesity among the offspring of diabetic mothers (ODM).To address this gap, we devised the Study of Women, Infant F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 89 publications
2
22
0
Order By: Relevance
“…Women with PEW have a larger amount of fat mass but achieve lower weight gain in pregnancy than pregnant women with PNW 36 . In our study, there was no intergroup difference in the overall absolute weight gain during pregnancy (PEW = 8.77 AE 7.38; PNW = 8.31 AE 3.81); however, women with PEW more often presented a higher level of weight gain during the third trimester than that recommended by the Institute of Medicine (P = 0.010; Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…Women with PEW have a larger amount of fat mass but achieve lower weight gain in pregnancy than pregnant women with PNW 36 . In our study, there was no intergroup difference in the overall absolute weight gain during pregnancy (PEW = 8.77 AE 7.38; PNW = 8.31 AE 3.81); however, women with PEW more often presented a higher level of weight gain during the third trimester than that recommended by the Institute of Medicine (P = 0.010; Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…All infants were healthy, live singleton births ≥35 weeks of gestation without serious medical conditions (e.g. failure to thrive, physical impairment affecting feeding ability, chronic infectious disease, severe jaundice or metabolic disorders) (18). Mothers provided written consent for three study visits at 6–9 weeks (baseline), 6 months and 12 months to measure their infant’s weight, length, three skin-fold thicknesses and head circumference, and completed surveys on infant behaviours and health.…”
Section: Methodsmentioning
confidence: 99%
“…These cut-offs are based on average milk intake of 24 oz among infants aged 6–9 weeks, such that >17 oz of formula represents >65%, and ≤6 oz of formula is ≤25% of the daily energy intake (20,21). As previously described (18), we classified exclusive or mostly BF as ‘intensive BF’ and exclusive or mostly FF as ‘intensive FF’ with <10% mixed feeders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GDM increases risks of perinatal complications and constitutes a risk for fetal macrosomia, shoulder dystocia and neonatal hypoglycemia (13). It is also demonstrated that women with a history of GDM have a high risk of developing dyslipidemia, obesity and insulin resistance as part of metabolic syndrome later in life (14,15). Due to the high risk for both the mother and fetus, its diagnosis and treatment during pregnancy should be managed accurately.…”
Section: Discussionmentioning
confidence: 99%